The Problems of Learning Mathematics through Online in the Covid-19 Pandemic Period - Nabila Dwi Utari; Wati Susilawati; Hamdan Sugilar (Gunung Djati Conference Series, 2022)
This study aims to find out the problems experienced by students and teachers in online mathematics learning during the COVID-19 pandemic and find solutions to overcome existing problems. The research method used in this research is a literature review. From the results of the study, it is known that the problems of learning mathematics experienced by students are difficulties in understanding the learning material, reduced activity, and motivation of students. Overcome these problems, it can be done by choosing appropriate and innovative learning methods, as well as by providing encouraging words that build students' learning motivation. The problems of learning mathematics experienced by teachers are difficulties in operating technology-based learning media, difficulties in explaining material online, and difficulties in giving assessments to students. Overcome these problems, it can be done by participating in seminars and training activities related to improving the skills of using learning media, making innovative learning videos, and using aspects of affective, cognitive, and psychomotor assessment.